PREVALENCE, SURGICAL MANAGEMENT, AND OUTCOME OF INTUSSUSCEPTION IN CHILDREN : A COMPREHENSIVE SYSTEMATIC REVIEW - Aisyah Sabrina, Syarifah Tiara; Jalaluddin Machalli, Muchammad; Nuraziza, Shafira; Melinda, Eza (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Intussusception is the invagination of a segment of bowel into an adjacent segment resulting into an intestinal obstruction. It is the most common acquired cause of intestinal obstruction in children under the age of 2 years. The aim: The aim of this study to show about prevalence, surgical management, and outcome of intussusception in children. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Ten publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Nonoperative management of intussusception should be adopted in carefully selected cases of intussusception in this subregion as it will help to reduce the financial burden on the parents while surgical management should be reserved for the complicated cases.